Concentration of Persistent Organic Pollutants in feathers of feral Greater Rheas in Northern Germany - Leche, Alvina (2025)
Concentration (ng/g) of POPs (Persistent Organic Pollutants) in Greather Rhea (Rhea americana) feathers from Germany. Analysis was done using a gas chromatograph coupled with a mass spectrometer.